17a+12b+4c+6c-6b-2a=

Simple and best practice solution for 17a+12b+4c+6c-6b-2a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17a+12b+4c+6c-6b-2a= equation:


Simplifying
17a + 12b + 4c + 6c + -6b + -2a = 0

Reorder the terms:
17a + -2a + 12b + -6b + 4c + 6c = 0

Combine like terms: 17a + -2a = 15a
15a + 12b + -6b + 4c + 6c = 0

Combine like terms: 12b + -6b = 6b
15a + 6b + 4c + 6c = 0

Combine like terms: 4c + 6c = 10c
15a + 6b + 10c = 0

Solving
15a + 6b + 10c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6b' to each side of the equation.
15a + 6b + -6b + 10c = 0 + -6b

Combine like terms: 6b + -6b = 0
15a + 0 + 10c = 0 + -6b
15a + 10c = 0 + -6b
Remove the zero:
15a + 10c = -6b

Add '-10c' to each side of the equation.
15a + 10c + -10c = -6b + -10c

Combine like terms: 10c + -10c = 0
15a + 0 = -6b + -10c
15a = -6b + -10c

Divide each side by '15'.
a = -0.4b + -0.6666666667c

Simplifying
a = -0.4b + -0.6666666667c

See similar equations:

| y=10(2x^2-1)(1-x)^2 | | 2/3-5/4= | | s=11+.5s | | 9x+47= | | 4m+3m=70 | | 4(1-4x)=4x-24 | | 20x-5-5(3x+11)=0 | | 5(3x+2)=7(2x+9) | | 2=2(3-2a) | | 5(x-1)+4x+3=79 | | 20p+11q+p-3q-6p= | | 2*sin*2x=-1 | | 16-6y=-9(7y-8) | | P(2)=-0.1x^5+3.8x^4+5000 | | 8x-6(2x-7)=-23 | | 8m+6n-3m+7n= | | -b^2+2b-6=0 | | 4y=7x^2-5 | | 4(2x+5)-7(x-3)= | | 8s-19=-25+6s | | 8(9+y)=7(y-3) | | sin(i)=0.4 | | 3t-3=-12+2t | | 2+2r=3-4r | | 3(n+4)=n+4 | | 14x+69=x | | 5z+3z=6z-7 | | x^3-4x^2-207x+630=0 | | 5x=88 | | 5x+2y+2z=7 | | 4(4x-8)-5=(x-3)+35 | | r+9.3=-0.5 |

Equations solver categories